Evaluation of three recombinant proteins for the development of ELISA and immunochromatographic tests for visceral leishmaniasis serodiagnosis - dos Santos, Anna Raquel Ribeiro (Mem Inst Oswaldo Cruz, 2019)
BACKGROUND: Visceral Leishmaniasis (VL) is an infectious disease that is a significant cause of death among infants aged under 1 year and the elderly in Brazil. Serodiagnosis is a mainstay of VL elimination programs; however, it has significant limitations due to low accuracy. OBJECTIVE: This study aimed to evaluate three recombinant Leishmania infantum proteins (rFc, rC9, and rA2) selected from previous proteomics and genomics analyses to develop enzyme-linked immunosorbent assay (ELISA) and immunochromatographic tests (ICT) for the serodiagnosis of human VL (HVL) and canine VL (CVL). METHODS: A total of 186 human (70 L. infantum-infected symptomatic, 20 other disease-infected, and 96 healthy) and 185 canine (82 L. infantum-infected symptomatic, 27 L. infantum-infected asymptomatic, and 76 healthy) sera samples were used for antibody detection. FINDINGS: Of the three proteins, rA2 (91.5% sensitivity and 87% specificity) and rC9 (95.7% sensitivity and 87.5% specificity) displayed the best performance in ELISA-HVL and ELISA-CVL, respectively. ICT-rA2 also displayed the best performance for HVL diagnosis (92.3% sensitivity and 88.0% specificity) and had high concordance with immunofluorescence antibody tests (IFAT), ELISA-rK39, IT-LEISH(®), and ELISA(EXT). ICT-rFc, ICT-rC9, and ICT-rA2 had sensitivities of 88.6%, 86.5%, and 87.0%, respectively, with specificity values of 84.0%, 92.0%, and 100%, respectively for CVL diagnosis. MAIN CONCLUSIONS: The three antigens selected by us are promising candidates for VL diagnosis regardless of the test format, although the antigen combinations and test parameters may warrant further optimisation.